Diagnostic value and clinical impact of cardiac magnetic resonance imaging in patients after sudden cardiac arrest: a retrospective study - Bernhard Strohmer; Reinhard Kaufmann; Elke Boxhammer; Richard Rezar; Stefan Hecht; Christoph Knapitsch; Nikolaos Schörghofer; Uta C Hoppe; Klaus Hergan; Bernhard Scharinger (Open Heart)
Introduction Cardiac MRI (CMRI) is an important investigation in cases of unclear cause of sudden cardiac arrest (SCA). It demonstrates diagnostic utility in assessing reversibility and tissue scar burden and ultimately aids in further treatment planning.Methods A retrospective analysis of all adult patients referred for CMRI after SCA between 2007 and 2022 by local intensive care units in our institution was performed. The patient cohort is highly selective, excluding those who did not reach the hospital, had cerebral oedema or had confirmed acute myocardial infarction as the cause of SCA. Data on clinical presentation, imaging findings and subsequent management were collected and analysed.Results CMRI was diagnostic in 57 of 65 patients. The most common diagnosis by CMRI was ischaemic cardiomyopathy (28.1%), followed by dilated cardiomyopathy (17.5%) and structurally normal hearts (14%). In cases of myocardial oedema, extracellular volume (ECV) was determined in 10 patients and found to be elevated in 80% after resuscitation, whereas T2 mapping was elevated in only 50% of cases. The number of examinations has increased, whereas the time to examination has decreased over the years. Additionally, CMRI findings led to changes in treatment planning.Conclusion CMRI after resuscitation is gaining increasing interest and clinical relevance as it provides additional diagnostic information that may be crucial for therapy planning. The sensitivity of ECV in detecting myocardial oedema after cardiac arrest highlights its potential utility over T2 mapping. Future studies should investigate the impact of CMRI on long-term patient outcomes and further refine its role in guiding treatment decisions.